The Development and Validation of the Workplace Ostracism Scale - FERRIS, Donald L. (Institutional Knowledge at Singapore Management University, 2008)
This article outlines the development of a 10-item measure of workplace ostracism. Using 6 samples (including multisource and multiwave data), the authors developed a reliable scale with a unidimensional factor structure that replicated across 4 separate samples. The scale possessed both convergent and discriminant validity, and criterion-related validity was demonstrated through the scale's relation with basic needs, well-being, job attitudes, job performance, and withdrawal. Overall, the present study suggests that the Workplace Ostracism Scale is a reliable and valid measure and that the workplace ostracism construct has important implications for both individuals and organizations. (PsycINFO Database Record (c) 2008 APA, all rights reserved). (from the journal abstract)